Evaluation of SDBS surfactant on coal wetting performance with static methods: Preliminary laboratory tests. Issue 23 (2nd December 2017) - Chen, Yinping; Xu, Guang; Albijanic, Boris
ABSTRACT: Coal dust contributes to lung diseases in coal miners. Spraying water mixed with surfactants is a method to suppress high concentration coal dust. This study presents the evaluation of the effect of SDBS surfactant on coals. Surfactant concentrations ranging from 0% to 1.0% were analyzed through the characterization of coal wettability and surfactant adsorption by using sink test, capillary penetration test, drop penetration test, surface tension test, and zeta potential test. Results show that SDBS surfactant greatly increased the coal wetting performance and the 0.02%-0.40% concentration was suggested as the optimum concentration range to improve coal wettability of coals.